ANALYSIS OF MARKETING STRATEGIES IN INCREASING SALES AT SIGER ROEMAH BATIK LAMPUNG - Rio Nopaldi; Vonny Tiara Narundana (ZILLZELL MEDIA PRIMA, 2024)
Lampung Batik has become a cultural heritage and creative industry that is rich in historical and artistic values. Siger Roemah Batik Lampung as one of the main players in this industry, plays an important role in preserving and developing the tradition of Lampung batik. This research aims to uncover ideas that can be implemented, in order to increase sales of Siger Roemah Batik Lampung. This research data comes from interviews, observations, all of which are qualitative approach methods. In this study, marketing mix, IFE/EFE analysis, SWOT analysis and QSPM Matrix were used as analytical tools on Internal and External aspects in Siger Roemah Batik Lampung Company. Siger Roemah Batik Lampung can take strategic steps based on the company's internal strengths and existing external opportunities, taking into account internal weaknesses and external threats that may occur. Thus, companies can optimize their potential and overcome the challenges faced within the company.